IOT based humidity and temperature control system for vegetables/fruits storage with ozone treatment - Chew, Boon Kee (2024)
Post-harvest storage is an important process in agriculture. However, the post-harvest process is usually done in conventional ways. IoT technology, as an emerging technology that is implemented in various fields, can be used to enhance the post-harvest process in agriculture. In other words, the shelf-life of the vegetables and fruits can be prolonged. A 15 days experiment has been conducted to investigate the effects of IoT cold storage chamber designed and ozone treatment in prolonging the shelf-life of vegetables in post-harvest process. In this experiment, two sets of cold storage chambers equipped with misting and cooling system controlled by Raspberry Pi were used to store butterhead lettuces. Monitoring and data collection of the internal environment have been done from time to time. One set of cold storage chamber used tap water for the misting system whereas the other was using ozonated water. The ozone treatment has been used to inhibit the growth of microorganisms to further improve the post-harvest storage process and it has been proven to be effectively prolong the shelf-life of the butterhead lettuces and also slowed down the quality deteriorations based on the appearance index measured. Thus, the design of the IoT cold storage chamber and ozone treatment were proven to be effective in the improvement of the post-harvest storage process. The practicality of the IoT cold storage chamber in agriculture has also been investigated during the project